Upaya Peningkatan Hasil Belajar Menyambut Usia Baligh melalui Pembelajaran Problem Based Learning (PBL) pada Siswa Kelas IV SDN 126/1 Penerokan - Ngadiah, Ngadiah; Sepriyanti, Nita; Riana, Novi (Lembaga Yasin AlSys, 2025)
This study aims to improve students' learning outcomes on the topic of approaching puberty through the implementation of the Problem-Based Learning (PBL) model in the fourth grade at SDN 126/1 Penerokan. The research method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The research subjects were 30 fourth-grade students. Data collection techniques included observation, interviews, learning outcome tests, and documentation, while data analysis was carried out descriptively using both quantitative and qualitative approaches. The results indicate that implementing the PBL model significantly enhanced students' learning activities, teacher performance, and learning outcomes. In the preliminary stage (pre-cycle), the student learning mastery level was only 40%, with an average score of 65. After applying the PBL model in Cycle I, improvements were observed, with the average score rising to 75 and the mastery level reaching 63.33%. However, challenges remained, such as students’ limited understanding of the PBL steps and minimal participation in group discussions. Adjustments were made in Cycle II, including the use of more interactive learning media, clearer teacher guidance, and increased student motivation. Consequently, the students' average score rose to 85, and the learning mastery level reached 100%. Student engagement during the learning process also improved from 70% in Cycle I to over 90% in Cycle II. Observations of teacher performance revealed that their ability to manage PBL-based learning increased from 80% in Cycle I to 95% in Cycle II. The study concludes that the Problem-Based Learning model significantly enhances students’ learning outcomes while fostering critical thinking, collaboration, and problem-solving skills. Based on the success achieved in both cycles, the research recommends broader implementation of the PBL model, particularly for topics requiring in-depth understanding, such as approaching puberty. This study also contributes to the development of innovative and contextual learning methods in primary schools.